Novel Feedback Calculation Technique for Improved Transmit Scheme - Eksim, Ali; Murat, Ertugrul (Společnost pro radioelektronické inženýrství, 2012)
Extended balanced space-time block coding (EBSTBC) is able to achieve large coding gain and guarantee full diversity for any number of transmit antennas. Performance of the EBSTBC has been improved with improved transmit scheme (ITS) which is combination of the EBSTBC with transmit antenna selection. Performance of the ITS with a limited number of feedback bits approaches to performance of ideal beamforming which requires ideal channel state information at the transmitter. However, the calculation of feedback information at the receiver employs exhaustive searching scheme which is very complex and energy inefficient process. In this work, a low complexity and energy efficient feedback information scheme for the ITS receiver is proposed. Theoretical and simulation results show that the calculation complexity of feedback information is decreased more than 87% and the proposed scheme yields the same bit error rate performance with the ITS. Moreover, the proposed scheme requires very low addition memory with respect to alternative schemes.
Keywords: Extended balanced space-time coding; feedback calculation; low complexity; energy efficiency.